2018
DOI: 10.1177/1060028018767899
|View full text |Cite
|
Sign up to set email alerts
|

A Blast From the Past: Revival of Angiotensin II for Vasodilatory Shock

Abstract: AT-II is a newly available vasoactive agent with a novel mechanism for the treatment of distributive shock. Further research is needed to define its exact role in therapy of shock states, identify patients most likely to benefit, and further study its safety profile in critical illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Most importantly, in vascular smooth muscle, stimulation results in direct arterial and venous vasoconstriction and an increase in systemic blood pressure, in addition to increased vascular permeability. 5,6 In the renal structures, angiotensin II stimulates sodium reabsorption and aldosterone release; in the pituitary, there is stimulation of vasopressin secretion from the posterior gland and adrenocorticotropic hormone secretion from the anterior gland; and in the cerebral circulation, there is stimulation of endogenous norepinephrine secretion. 5,6 Even though catecholamines are known to constrict the mesenteric vasculature, it has been suggested that angiotensin II may mobilize venous blood from the mesenteric circulation and in turn increase preload and promote lactate clearance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, in vascular smooth muscle, stimulation results in direct arterial and venous vasoconstriction and an increase in systemic blood pressure, in addition to increased vascular permeability. 5,6 In the renal structures, angiotensin II stimulates sodium reabsorption and aldosterone release; in the pituitary, there is stimulation of vasopressin secretion from the posterior gland and adrenocorticotropic hormone secretion from the anterior gland; and in the cerebral circulation, there is stimulation of endogenous norepinephrine secretion. 5,6 Even though catecholamines are known to constrict the mesenteric vasculature, it has been suggested that angiotensin II may mobilize venous blood from the mesenteric circulation and in turn increase preload and promote lactate clearance.…”
Section: Discussionmentioning
confidence: 99%
“…4 Angiotensin II acts directly on vessel walls, resulting in vasoconstriction and, most importantly, a rise in mean arterial pressure (MAP)-independent of adrenergic stimulation. 5,6 Given this, herein the authors report their experience with the use of synthetic human angiotensin II infusion for vasopressor refractory vasoplegic shock in patients undergoing cardiothoracic surgery requiring CPB. In all cases, a MAP of at least 65 mmHg was targeted with angiotensin II infusion, and norepinephrine was preferentially down-titrated as hemodynamics allowed.…”
mentioning
confidence: 99%
“…Sepsis also leads to an imbalance between vascular mediators. Vasodilating factors (e.g., nitric oxide, tumor necrosis factor-α, histamine, kinins, and prostaglandins) are released, whereas the vasoconstrictor response to ATII and catecholamines might decrease [5-6]. Refractory septic shock is associated with impaired microvascular flow and reduced capillary density at sub pressor levels [7].…”
Section: Discussionmentioning
confidence: 99%
“…The newest agent approved by the US Food and Drug Administration (FDA) for sepsis and other vasodilatory shock is synthetic human angiotensin II (ATII), which offers a novel mechanism of action by promoting vasoconstriction and fluid retention through the renin-angiotensin-aldosterone system. 25 The drug was granted FDA approval based on results of the Angiotensin II for the Treatment of High-Output Shock (ATHOS-3) study. 26 A total of 321 patients were enrolled to receive ATII or placebo in addition to vasopressors.…”
Section: Angiotensin IImentioning
confidence: 99%